Trade-Off Between Photosynthetic Promotion and Nitrogen Fixation Suppression Induced by Chloroplast-Targeted Mo Nanoparticles in Soybean - Kan Huang; Chengxiao Hu; Qiling Tan; Songwei Wu; Sergey Shabala; Min Yu; Xuecheng Sun (Journal of Hazardous Materials, 2026)

Integrated mineralogical, metabolomic, and gene expression analysis of the phosphate-solubilizing mechanism of Pseudomonas sp. PSB-13 - Qingyun Xu; Youyou Zhao; Chengxiao Hu; Songwei Wu; Qiling Tan; Xuecheng Sun (World Journal of Microbiology and Biotechnology, 2026)

The crucial roles of citrus branch compost in enhancing soil nutrients, optimizing microbial community structure, and improving fruit quality over its raw materials - Jinye Li; Songwei Wu; Jixiang Zheng; Xuecheng Sun; Qiling Tan; Chengxiao Hu (Plant and Soil, 2026)

MoS2@Fe3O4 nanozyme redirects carbon to strengthen symbiotic nitrogen fixation in soybean for fertilizer-minimizing cleaner production - Kan Huang; Yining Liu; Youyou Zhao; Qingyun Xu; Chengxiao Hu; Qiling Tan; Songwei Wu; Sergey Shabala; Min Yu; Xuecheng Sun (Journal of Cleaner Production, 2026)

Lake Water Depth and Nutrient Gradients Mediate Aquatic Plant Distribution via the Strength of Trait Network Associations - Guixiang Yuan; Huan Long; Jun Liu; Qiling Xie; Yaoxuan Tan; Zihui Hong; Jiahui Yue; Aimin Zhou; Hexuan Zhou; Weilin Xu; Bao Wang; Huanyao Liu; et al. (Global Change Biology, 2026)
Aquatic macrophyte responses and adaptation to water depth and nutrient gradients are of critical importance for understanding the functional ecology of lakes and their restoration when degraded. However, the role of plant trait networks (PTNs), a powerful tool for decoding trait–environment–function relationships, in mediating these adaptations remains unclear, particularly across species and community scales. We conducted cross‐scale PTN analyses at species and community levels for aquatic macrophytes, integrating assessments of phylogenetic signals and hierarchical environmental filtering. At species level, aquatic macrophytes exhibited two complementary PTN‐based adaptive strategies: trait compartmentalization to enhance stress tolerance and trait integration to optimize resource utilization. Notably, local environmental conditions (rather than phylogenetic signals) dominated the pattern of PTN metrics, highlighting the primacy of immediate habitat constraints over evolutionary relatedness in driving species‐specific adaptations. At community level, environmental filtering operated hierarchically, acting sequentially by water depth, nutrient availability, and lake morphology. PTNs further mediated the trade‐off between community diversity and productivity, providing a mechanistic link between abiotic filtering and ecosystem function. Our findings advance network theory in functional ecology by extending its application to aquatic systems, bridging longstanding gaps between terrestrial and aquatic PTN research, and offering actionable guidance for eutrophic lake restoration (e.g., by targeting PTN‐linked core traits related to nutrient adaptation). Overall, our work provides a cross‐scale framework for understanding PTN mediated adaptation of aquatic macrophytes and its implications for ecosystem management.

Effects of protein-bound iron supplementation on reproductive performance of sows and growth performance of piglets - Hongxuan Ye; Junyi Wu; Xuexun Feng; Qiling Chen; Zihao Huang; Bin Su; Songfeng Yang; Lili Wang; Hefeng Luo; Chengquan Tan (Domestic Animal Endocrinology, 2026)

Molybdenum tolerance of strains screened from molybdenum tailings and their potential application in molybdenum-contaminated soils - Xiaomei Zheng; Songwei Wu; Qiling Tan; Chengxiao Hu; Xuecheng Sun (Environmental Pollution, 2025)

Adsorption properties and availability changes of molybdenum oxide nanoparticles in acidic yellow-brown soil - Xiaomei Zheng; Songwei Wu; Qiling Tan; Chengxiao Hu; Xuecheng Sun (Journal of Soils and Sediments, 2025)

The carbon footprint and ecological costs of citrus production in China are going down - Jinye Li; Shanshan Liang; Xiaomin Liang; Xiaojuan Wang; Xinchen Bai; Yilin Chen; Kongjie Wu; Xiaoman Liu; Zhihao Dong; Qiling Tan; Xuecheng Sun; Chengxiao Hu; et al. (Journal of Cleaner Production, 2025)

Difference in soil microbial necromass carbon accumulation induced by three crops straw mulching for 4 years in a citrus orchard - Xiaomin Liang; Yilin Chen; Xiaojuan Wang; Qiling Tan; Songwei Wu; Chengxiao Hu (Biology and Fertility of Soils, 2024)

Combined dynamic transcriptome and flavonoid metabolome reveal the role of Mo nanoparticles in the nodulation process in soybean - Yining Liu; Songwei Wu; Xiaoming Qin; Min Yu; Sergey Shabala; Xiaomei Zheng; Chengxiao Hu; Qiling Tan; Shoujun Xu; Xuecheng Sun (Science of The Total Environment, 2024)

Nano molybdenum trioxide-mediated enhancement of soybean yield through improvement of rhizosphere soil molybdenum bioavailability for nitrogen-fixing microbial recruitment - Qibiao Li; Kan Huang; Zhichen Liu; Xiaoming Qin; Yining Liu; Qiling Tan; Chengxiao Hu; Xuecheng Sun (Science of The Total Environment, 2024)

The pivotal role of secondary nutrients and micronutrients in regulating fruit quality and root exudates metabolism profile of citrus - Yanni Tang; Wei Lou; Xiang Yan; Shiqian Li; Pengwei Wang; Yingjie Zhou; Ting Zhan; Siming Zhang; Chengxiao Hu; Xu Wang; Hanliang Liu; Qiling Tan; et al. (Plant and Soil, 2024)

Transcriptomic-metabolomic analysis of magnesium-stimulated in peel coloration of Satsuma mandarin - Xiaoman Liu; Chengxiao Hu; Xiaodong Liu; Yuan Zhou; Qiling Tan; Xuecheng Sun; Songwei Wu (Postharvest Biology and Technology, 2023)

The role of phosphorus speciation of biochar in reducing available Cd and phytoavailability in mining area soil: Effect and mechanism - Kan Huang; Xuecheng Sun; Jingguo Sun; Yali Guo; Xiaoming Hu; Chengxiao Hu; Qiling Tan (Science of The Total Environment, 2023)

Soil nematode abundances drive agroecosystem multifunctionality under short‐term elevated CO 2 and O 3 - Jianqing Wang; Xiuzhen Shi; Manuel Esteban Lucas‐Borja; Qiling Guo; Jiaoyan Mao; Yunyan Tan; Guoyou Zhang (Global Change Biology, 2023)
The response of soil biotas to climate change has the potential to regulate multiple ecosystem functions. However, it is still challenging to accurately predict how multiple climate change factors will affect multiple ecosystem functions. Here, we assessed the short‐term responses of agroecosystem multifunctionality to a factorial combination of elevated CO 2 (+200 ppm) and O 3 (+40 ppb) and identified the key soil biotas (i.e., bacteria, fungi, protists, and nematodes) concerning the changes in the multiple ecosystem functions for two rice varieties (Japonica, Nanjing 5055 vs. Wuyujing 3). We provided strong evidence that combined treatment rather than individual treatments of short‐term elevated CO 2 and O 3 significantly increased the agroecosystem multifunctionality index by 32.3% in the Wuyujing 3 variety, but not in the Nanjing 5055 variety. Soil biotas exhibited an important role in regulating multifunctionality under short‐term elevated CO 2 and O 3 , with soil nematode abundances better explaining the changes in ecosystem multifunctionality than soil biota diversity. Furthermore, the higher trophic groups of nematodes, omnivores‐predators served as the principal predictor of agroecosystem multifunctionality. These results provide unprecedented new evidence that short‐term elevated CO 2 and O 3 can potentially affect agroecosystem multifunctionality through soil nematode abundances, especially omnivores‐predators. Our study demonstrates that high trophic groups were specifically beneficial for regulating multiple ecosystem functions and highlights the importance of soil nematode communities for the maintenance of agroecosystem functions and health under climate change in the future.

Recruitment of specific microbes through exudates affects cadmium activation and accumulation in Brassica napus - Songwei Wu; Kongjie Wu; Libiao Shi; Xuecheng Sun; Qiling Tan; Chengxiao Hu (Journal of Hazardous Materials, 2023)

Effects of soil amendments on soil fertility and fruit yield through alterations in soil carbon fractions - Xiaomin Liang; Qin Chen; Muhammad Shoaib Rana; Zhihao Dong; XiaoDong Liu; Chengxiao Hu; Qiling Tan; Xiaohu Zhao; Xuecheng Sun; Songwei Wu (Journal of Soils and Sediments, 2021)

Arbuscular mycorrhizal fungi and its major role in plant growth, zinc nutrition, phosphorous regulation and phytoremediation - Parashuram Bhantana; Muhammad Shoaib Rana; Xue-cheng Sun; Mohamed G. Moussa; Muhammad Hamzah Saleem; Muhamad Syaifudin; Ashrafuzzaman Shah; Amrit Poudel; Amar Bahadur Pun; Mufid Alam Bhat; Dhanik Lal Mandal; Sujit Shah; et al. (Symbiosis, 2021)

Effects of Molybdenum on Cell Wall Component of Wheat Leaf Under Different Growth Stages - Xiaozhen Yang; Qiaoqiao Gan; Xuecheng Sun; Songwei Wu; Qiling Tan; Chengxiao Hu (Journal of Soil Science and Plant Nutrition, 2021)

Research on the nitrogen transformation in rhizosphere of winter wheat (Triticum aestivum) under molybdenum addition - Xin Wen; Chengxiao Hu; Xuecheng Sun; Xiaohu Zhao; Qiling Tan (Environmental Science and Pollution Research, 2019)

Nitric oxide acts downstream of abscisic acid in molybdenum-induced oxidative tolerance in wheat - Songwei Wu; Chengxiao Hu; Qiling Tan; Xiaohu Zhao; Shoujun Xu; Yitao Xia; Xuecheng Sun (Plant Cell Reports, 2018)

Molybdenum-induced alteration of fatty acids of thylakoid membranes contributed to low temperature tolerance in wheat - Songwei Wu; Siqi Wei; Chengxiao Hu; Qiling Tan; Tianwu Huang; Xuecheng Sun (Acta Physiologiae Plantarum, 2017)

Effect of NO3 −:NH4 + ratios on growth, root morphology and leaf metabolism of oilseed rape (Brassica napus L.) seedlings - Shiyu Qin; Xuecheng Sun; Chengxiao Hu; Qiling Tan; Xiaohu Zhao; Juan Xin; Xin Wen (Acta Physiologiae Plantarum, 2017)

The Effects of Cadmium Exposure on Cadmium Fractionation and Enzyme Activities in the Rhizosphere of Two Radish Cultivars (Raphanus sativus L.) - Juan Xin; Xiaohu Zhao; Qiling Tan; Xuecheng Sun; Xin Wen; Shiyu Qin; Chengxiao Hu (Bulletin of Environmental Contamination and Toxicology, 2017)

The response of ammonia-oxidizing microorganisms to trace metals and urine in two grassland soils in New Zealand - Pengcheng Wang; Hong J. Di; Keith C. Cameron; Qiling Tan; Andriy Podolyan; Xiaohu Zhao; Ron G. McLaren; Chengxiao Hu (Environmental Science and Pollution Research, 2017)

Drought stress tolerance mediated by zinc-induced antioxidative defense and osmotic adjustment in cotton (Gossypium Hirsutum) - Songwei Wu; Chengxiao Hu; Qiling Tan; Lu Li; Kaili Shi; Yong Zheng; Xuecheng Sun (Acta Physiologiae Plantarum, 2015)

Differences in responses of soil microbial properties and trifoliate orange seedling to biochar derived from three feedstocks - Ying Zhang; Qiling Tan; Chengxiao Hu; Cangsong Zheng; Huiping Gui; Weinan Zeng; Xuecheng Sun; Xiaohu Zhao (Journal of Soils and Sediments, 2015)

Differential Expression of Proteins in Response to Molybdenum Deficiency in Winter Wheat Leaves Under Low-Temperature Stress - Xuecheng Sun; Qiling Tan; Zhaojun Nie; Chengxiao Hu; Yongqiang An (Plant Molecular Biology Reporter, 2014)

Molybdenum improves antioxidant and osmotic-adjustment ability against salt stress in Chinese cabbage (Brassica campestris L. ssp. Pekinensis) - Mu Zhang; Chengxiao Hu; Xiaohu Zhao; Qiling Tan; Xuecheng Sun; Anyong Cao; Min Cui; Ying Zhang (Plant and Soil, 2012)

Effective mitigation of nitrate leaching and nitrous oxide emissions in intensive vegetable production systems using a nitrification inhibitor, dicyandiamide - Min Cui; Xuecheng Sun; Chengxiao Hu; Hong J. Di; Qiling Tan; Changsheng Zhao (Journal of Soils and Sediments, 2011)

Interactive effects of molybdenum and phosphorus fertilizers on photosynthetic characteristics of seedlings and grain yield of Brassica napus - Hongen Liu; Chengxiao Hu; Xuecheng Sun; Qiling Tan; Zhaojun Nie; Xiaoming Hu (Plant and Soil, 2010)

A lysimeter study of nitrate leaching and optimum nitrogen application rates for intensively irrigated vegetable production systems in Central China - Changsheng Zhao; Chengxiao Hu; Wei Huang; Xuecheng Sun; Qiling Tan; Hongjie Di (Journal of Soils and Sediments, 2010)